Influences of Synchronized Metronome Training on Soccer Players’ Timing Ability, Performance Accuracy, and Lower-Limb Kinematics - Rönnqvist, Louise; McDonald, Rachel; Sommer, Marius (Frontiers in Psychology, 2018)
Planning and performance of all complex movement requires timing, integration and coordination between sensory-perception and motor production to be successful. Despite this, there is limited research into “if” and “how” timing training may influence movement performance in athletes. The aim of the present study was to investigate the effect of synchronized metronome training (SMT) on sensorimotor timing ability, and in view of that, if improved timing may be transferred to lower-limb movement performance and kinematics. The sample consisted of twenty-four female elite- and semi-elite soccer players, randomly assigned to receive SMT and a control group. The SMT group received 12 hours of Interactive Metronome® (IM) training over four weeks. At pre- and post-test, timing-precision was assessed through hand and feet movement synchronization with rhythmic sound; and leg-movements performance accuracy, duration and kinematics were recorded during embodied high cognitive-load stepping task (6 trials x 20s) by using an optoelectronic motion capture system. Pre- to post-test comparisons showed significant timing improvements as an effect of the IM training. Significant pre- to post-test improvements on the stepping task performance were found by increasing number of accurate foot taps during the stepping task and by shorter performance duration for the SMT-group only. No evident pre- to post-test effects of SMT on the kinematic parameters investigated were found. These findings signify that the cognitive control functions may be positively affected of the SMT training; resulting in better motor planning-performance and movement precision. Still, independently of group and test-occasion, significant correlations were found between participants’ performance differences and the kinematic parameters by means of decreasing 3D movement distance and less segmented movements correlated negatively, and increasing velocity (speed) positively, with accuracy and performance duration respectively. These findings are likely associated with inter-individual variations in the nature of higher-order cognitive processing capacity due to the demands of the cognitive-load added to the stepping task.